Knowledge mapping of students’ mental health status in the COVID-19 pandemic: A bibliometric study - Yang, Yang; Cao, Qingtai; Zhao, Mingyi; Zhuang, Quan (Frontiers in Psychology, 2022)
Objective The purpose of this study was to investigate the international scientific output on mental health of students during COVID-19 from 2020 to 2022 through a bibliometric analysis and to explore trend and research hotspots in this field. Methods We searched the Web of Science Core Collection for publications and used a variety of software to analyze and visualize the data such as R, CiteSpace, VOSviewer and Scimago. Results A total of 2,734 publications were retrieved as of June 4, 2022, published by 3,894 institutions from 120 countries/regions. China and the United States lead in the quantity and quality of publications in this field. According to Bradford’s Law, 16 journals are considered core journals in the field. Co-cited references indicate the main psychological problems of students under the epidemic revolve around anxiety, poor sleep and financial difficulty. Their behavior might also be influenced by increased internet and alcohol use. Conclusion Mental health of students during COVID-19 is attracting increasing attention. It is identified that the research hotspots in this field continue to revolve around emotional anxiety and unhealthy behaviors. Due to the different troubles faced by different groups under COVID-19, further exploration of the relevant factors specific for students are needed, with a hopeful view to providing ideas for intervention measures.